2017
DOI: 10.1017/iop.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Blaming the Victim: Toward a More Progressive Understanding of Workplace Mistreatment

Abstract: Theories of human aggression can inform research, policy, and practice in organizations. One such theory, victim precipitation, originated in the field of criminology. According to this perspective, some victims invite abuse through their personalities, styles of speech or dress, actions, and even their inactions. That is, they are partly at fault for the wrongdoing of others. This notion is gaining purchase in industrial and organizational (I-O) psychology as an explanation for workplace mistreatment. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(145 citation statements)
references
References 60 publications
(115 reference statements)
1
134
0
10
Order By: Relevance
“…Originating within the field of criminology, this model explains the occurrence of criminal behavior by arguing that victim traits and behaviors can precipitate a victim's own experiences of crime and maltreatment. Though this model was initially popular among criminologists, scholars began criticizing the implications of the victim precipitation ideology as early as the 1970s (Cortina, Rabelo, & Holland, 2018). According to these critics, victim precipitation thinking encourages victim blaming, offers inadequate logical and empirical evidence, and provides little practical insight into predicting and combating crime (e.g., Timmer & Norman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Originating within the field of criminology, this model explains the occurrence of criminal behavior by arguing that victim traits and behaviors can precipitate a victim's own experiences of crime and maltreatment. Though this model was initially popular among criminologists, scholars began criticizing the implications of the victim precipitation ideology as early as the 1970s (Cortina, Rabelo, & Holland, 2018). According to these critics, victim precipitation thinking encourages victim blaming, offers inadequate logical and empirical evidence, and provides little practical insight into predicting and combating crime (e.g., Timmer & Norman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model of instigated incivility tested in this research suggested that employees with strong social dominance traits are more likely to instigate uncivil workplace behavior Hu & Liu, 2017;Shao et al, 2011). The model also explored how or why instigated incivility unfolds within organizations and suggested that uncivil behavior may be explained by the emotion regulation strategies of cognitive reappraisal and expressive suppression (Grandey, 2000;Grandey & Gabriel, 2015;Van Hiel et al, 2006), and that norms of workgroup civility climate may specify when instigated incivility occurs (Cortina et al, 2018;Walsh et al, 2012;2018).…”
Section: Summary Of the Studymentioning
confidence: 78%
“…Employee emotions are identified as leverage points for HRD practitioners to reduce instigated incivility within organizations (Reio & Ghosh, 2009). Workgroup civility climate norms (Cortina, Rabelo, & Holland, 2018;Walsh et al, 2012Walsh et al, , 2018 and emotion regulation strategies may explain the trajectory of workplace behaviors (Grandey, 2000;Grandey & Gabriel, 2015). Instigated incivility research might yield new insights into the implementation of policies and practices to reduce its likelihood in the workplace (Cortina et al, 2018).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations